(untitled) (Jurnal Adabiya, 2020)
Building the literacy of rural communities is the responsibility of universities as one of Tri Dharma Perguruan Tinggi. This paper examines how to build rural livelihoods based on experience from community engagement programs undertaken by universities in Cot Lamme village, Aceh Besar. From the results of this program it can be proved that the Taman Bacaan (TABACA) of the Cot Lamme Village Society has been established permanently and the formation of Taman Bacaan (TABACA) volunteers. who sincerely and voluntarily manage the current reading garden and its sustainability in the future. The result of this program has also compiled the organizational structure of Taman Bacaan (TABACA) whose members are entirely derived from the managing volunteers. Ultimately the program established strong togetherness and commitment between the management volunteers and the leaders of the Cot Lamme village as well as the development of a new reading interest culture in the community, so it is expected to foster the spirit of literacy in reading the community and the role of TABACA can really strengthen the knowledge of civil society and an enlightened generation in the future.